Cap-assisted endoscopy: Do we have enough evidence? - Frieling, Thomas (Endoscopy International Open, 2018)
So, is there enough evidence to incorporate CC in clinical practice? If we interpret the literature and the meta-analysis by Nutalapati et al., the answer for the clinically-focused endoscopist, with regard to adenoma detection rate (ADR), at present, may be “no”. Significant differences do not necessarily imply clinical benefits and translation into clinical practice. The answer for the improvement of cecal intubation frequency and intubation time by the cap depends on the focus of training commitment, because these effects of the cap may be beneficial, especially for unexperienced endoscopists. It is obvious that further studies are needed. In this line, it is interesting to know, that in a recent meta-analysis of prospective studies, the length of the transparent cap had opposite effects on investigation time and polyp detection rate. Whereas, the anal to cecal time was significantly shortened by a cap length of > 7 mm and a polyp detection rate was significantly improved by a cap length of < 4 mm.